Commodity advertising pays… or does it? What it takes to keep those raisins dancing - Hoy Carman; Richard Green; Gay J. Mandour (California Agriculture, 1992)
California's farmers collectively spend more than $100 million a year to promote their products. Here are answers to such questions as: Where is the money spent? What are the public policy issues associated with government-sponsored generic commodity advertising? How successful are those campaigns? And finally, how can commodity groups improve their data bases?